On improving the pension system in the Russian Federation - Milshin, Yuri N. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. Pension legislation has undergone major changes over the past two decades. The changes were aimed at improving the quality of well-being of citizens of retirement age. At the same time, the uncodified and unsystematic nature of pension legislation creates certain obstacles to the realization of the pension rights. The pension legislation system needs fundamental changes to ensure effective social guarantees for pensioners. Theoretical analysis. Modern pension legislation requires fundamental study and systematization, which makes it possible to establish uniform principles of pension provision. The uniform requirements should equally protect the pension rights of all citizens. The development of pension legislation should be based on the principle of fair pension payments. The author considered the features of pension provision for certain categories of subjects and the positive experience of foreign countries. Empirical analysis. The research revealed that the problems of modern pension legislation are manifested in the absence of a systematic approach to the development of theoretical provisions and legal mechanisms to ensure the social security of pensioners. The complexity and unpredictability of pension legislation leads to the unwillingness of potential pensioners to pay taxes in good faith and earn retirement experience. Results. The study yielded the justification of the need to codify the current pension legislation, develop common principles of pension provision, taking into account the fair contribution of a person to all spheres of society. The adoption of the Pension Code of the Russian Federation was justified.